Detection of new Yr1-virulences in Puccinia striiformis f. sp. tritici population and its sources of resistance in advance wheat lines and released cultivars - S.C. BHARDWAJ*, PRAMOD PRASAD, HANIF KHAN, SIDDANNA SAVADI and S.K. SHARMA, O.P. GANGWAR, SUBODH KUMAR (Indian Phytopathology, 2017)
Five hundred and eight yellow rust (YR) samples were pathotyped from Northern states of India during 2014-15 and 2015-16 cropping seasons. The virulence of these samples was tested on 16 wheat differentials and 6 supplementary varieties. Eleven known pathotypes were identified from the analysis of 508 YR samples during this period. Additionally, the infection types of three samples on differentials, collected from US Nagar (Uttarakhand), Kangra and Kinnaur (Himachal Pradesh) districts, were dissimilar to the known pathotypes in India. Subsequently, three isolations were taken from each sample, established separately on susceptible check (A-9-30-1) and each isolation was used to inoculate differentials. All the isolations taken from single sample, showed similar reaction types on differentials. It proved the presence of new pathotype. The new pathotypes (virulences) were designated as 111S68, 79S4 and 79S68. Rust resistance genes Yr2 (Heines VII), Yr5, Yr9, Yr10, Yr15, Yr24, YrA were found effective to all these new pathotypes, identified in this study. Evaluation of 135 advance lines and released varieties of bread, durum, dicoccum wheat and triticale indicated that new pathotypes (111S68, 79S4, and 79S68) were less virulent than known pts. 47S103 (T) and 47S102 (K) virulent to Yr1. More than 70 per cent evaluated wheat and triticale material was found resistant to moderately resistant to all Yr1-virulences. New pathotypes, identified from indigenous wheat, would aid in understanding the evolution mechanism in Yr1-virulences of yellow rust pathogen in India for better management of yellow rust.